Simulating the Turbulent Hydrothermal Behavior of Oil/MWCNT Nanofluid in a Solar Channel Heat Exchanger Equipped with Vortex Generators - Maouedj, Rachid; Menni, Younes; İnç, Mustafa; Chu, Yu-Ming; Ameur, Houari; Lorenzini, Giulio (Tech Science Press, 2021)
Re-engineering the channel heat exchangers (CHEs) is the goal of many recent studies, due to their great importance in the scope of energy transport in various industrial and environmental fields. Changing the internal geometry of the CHEs by using extended surfaces, i.e., VGs (vortex generators), is the most common technique to enhance the efficiency of heat exchangers. This work aims to develop a newdesign of solar collectors to improve the overall energy efficiency. The study presents a new channel design by introducing VGs. The FVM (finite volume method) was adopted as a numerical technique to solve the problem, with the use ofOil/MWCNT(oil/multi-walled carbon nano-tubes) nanofluid to raise the thermal conductivity of the flow field. The study is achieved for a Re number ranging from12x10(3) to 27x10(3), while the concentration (phi) of solid particles in the fluid (Oil) is set to 4%. The computational results showed that the hydrothermal characteristics depend strongly on the flow patterns with the presence of VGs within the CHE. Increasing the Oil/MWCNT rates with the presence of VGs generates negative turbulent velocities with high amounts, which promotes the good agitation of nanofluid particles, resulting in enhanced great transfer rates.
Keywords: Channel heat exchanger; forced-convection; Oil; MWCNT nanofluid; CFD; vortex generators